Tuberculosis infection following immune checkpoint inhibitor treatment for advanced cancer: a case report and literature review - Lin, Chen; Xu, Guixiang; Gao, Shuyan; Feng, Tao; Li, Shuang (Frontiers in Immunology, 2023)
Objective To investigate the clinical features of active tuberculosis (TB) infection due to immune checkpoint inhibitors (ICIs) treatment in patients with advanced cancer. Methods We report the diagnosis and treatment of a case of pulmonary malignancy (squamous cell carcinoma, cT4N3M0 IIIC), secondary to active TB infection following ICIs therapy. Moreover, we summarize and analyze other related cases collected from the China National Knowledge Infrastructure (CNKI), Wanfang Database, PubMed, the Web of Science, and EMBASE (up to October 2021). Results A total of 23 patients, including 20 males and 3 females who were aged 49-87 years with a median age of 65 years, were included in the study. Twenty-two patients were diagnosed by Mycobacterium tuberculosis culture or DNA polymerase chain reaction (PCR), while the remaining patient was diagnosed by tuberculin purified protein derivative and pleural biopsy. One case had an interferon-gamma release assay (IGRA) to rule out latent TB infection prior to the application of ICI. Fifteen patients received an anti-tuberculosis regimen. Among the 20 patients with a description of clinical regression, 13 improved and 7 died. Seven of the patients who improved were treated with ICI again and four of them did not experience a recurrence or worsening of TB. The case diagnosed in our hospital also improved after receiving anti-TB treatment after stopping ICI therapy, and continued chemotherapy on the basis of anti-TB treatment, and his condition is relatively stable at present. Conclusion Due to the lack of specificity of TB infection following ICIs therapy, patients should be followed for fever and respiratory symptoms for 6.3 months after drug administration. It is recommended that IGRA should be performed before ICIs therapy and the development of TB during immunotherapy in patients who are positive in IGRA should be closely monitored. The symptoms of TB in most patients can be improved with ICIs withdrawal and anti-TB treatment, but there is still a need to be alert to the potentially fatal risk of TB.